ANALISIS KESESUAIAN KONTEN BUKU TEKS BIOLOGI KELAS XI SMA TERHADAP KURIKULUM 2013 - Nurjannah, Suci Nurjannah; Febriani, Husnarika; Rohani, Rohani (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
This study aims to determine the suitability of the content of biology textbooks for class XI SMA to the curriculum 2013. The type of research used is descriptive research with a qualitative approach and uses content/document analysis methods. The subject of this research is a biology textbook for class XI high school with cell material consisting of 3 books to be analyzed by researchers, namely the book publisher Bumi Aksara, the book publisher Erlangga, and the book publisher Grafindo Media Pratama. The research instrument used was an analysis sheet of student books based on the Curriculum 2013 Implementation Assistance Activity Guidelines. The results showed that the level of conformity of the content of biology textbooks based on: (1) SKL aspects in books A and B was 93% (very appropriate), and book C was 87% (very suitable). (2) Aspects of Core Competence for book A are 92% (very suitable), and books B and C are 83% (appropriate). (3) Aspects of Basic Competence for Book A 96% (very suitable), book B 85% (very suitable), book C 89% (very suitable). (4) Aspects of Sufficiency of Material for book A 67% (appropriate), books B and C for 50% (not appropriate). (5) Aspect of Material Depth of Book A 75% (appropriate), book B 68% (appropriate), and Book C 71% (appropriate). (6) Aspects of the Scientific Approach of books A, B, and C by 100% (very appropriate). (7) The authentic assessment aspect of Book A is 57% (quite appropriate), book B is 54% (not suitable) and C is 59% (quite appropriate). The average agreement coefficient of the three books is 0.94% (very good). The data illustrates that the three books can be recommended by the 2013 curriculum formulation. Kata kunci: Analisis Kesesuaian Konten, Buku Teks Biologi, Kurikulum 2013